2018
DOI: 10.3390/epigenomes2040020
|View full text |Cite
|
Sign up to set email alerts
|

On the Cooperation between Epigenetics and Transcription Factor Networks in the Specification of Tissue Stem Cells

Abstract: It is generally accepted that epigenetic modifications, such as DNA and histone methylations, affect transcription and that a gene’s transcription feeds back on its epigenetic profile. Depending on the epigenetic modification, positive and negative feedback loops have been described. Here, we study whether such interrelation are mandatory and how transcription factor networks affect it. We apply self-organizing map machine learning to a published data set on the specification and differentiation of murine inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 36 publications
2
27
0
Order By: Relevance
“…Changes of methylation with only minor effect on transcription was found for GPCRs also upon cell differentiation. Overall we find striking agreement between gene functions in these three regimes between cell developmental data [57], WHO grade IV GBM [26] and the LGG studied here. Interestingly, methylation seems to-activate enhancers in TF-networks while it de-activates enhancers for developmental processes [72] or, in other words, enhancer and promoter methylation seem to act in an antagonistic fashion for both types of processes.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Changes of methylation with only minor effect on transcription was found for GPCRs also upon cell differentiation. Overall we find striking agreement between gene functions in these three regimes between cell developmental data [57], WHO grade IV GBM [26] and the LGG studied here. Interestingly, methylation seems to-activate enhancers in TF-networks while it de-activates enhancers for developmental processes [72] or, in other words, enhancer and promoter methylation seem to act in an antagonistic fashion for both types of processes.…”
Section: Discussionsupporting
confidence: 77%
“…They revealed the largest diversity and were divided into four expression (E2-E5) and three methylation (M2-M4) subtypes, which only partly match each other, thus reflecting partly decoupled expression and methylation patterns due to different possible interaction mechanisms [26, 57]. Particularly, decoupling between transcription and methylation can be rationalized in terms of independent regulation mechanisms of transcription by epigenetic and transcription factor (TF)-networks which are governed by bistable epigenetic switches [57]. Applying this model to cell differentiation data we recently identified situations where variant transcription of genes is accompanied by invariant epigenetic promoter states or vice versa.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of gene expression patterns during development are governed by epigenetic mechanisms in cooperation with regulation via transcription factor networks [32,33]. Particularly, we found that gene signatures of epigenetic impact, such as targets of the polycomb repressive complex 2 (PRC2), of H3K27me3, and of bivalently (H3K4me3 and H3K27me3) marked gene promoters, have an almost antagonistic expression profile as compared to the stemness signatures (Figure 4A, in comparison to Figure 1F).…”
Section: Resultsmentioning
confidence: 94%
“…Differences of biological mechanisms behind transcriptomic [11] and the epigenetic predictors [71] of ageing or disease progression are not completely clear [11]. We recently reported that transcriptomic and epigenetic mechanisms partly decouple in cancer development [72,73] and cell differentiation [50]. Thus, the expression changes observed might reflect changed chromatin organization leading to altered cell function in type 1 compared with type 2 as discussed, e.g., as epigenetic mechanisms accompanying ageing [74] and inflammation [75][76][77][78] and associating with changes of DNA-methylation and histonemarks governing gene activity.…”
Section: Epigenetic Background and Ageing Clocksmentioning
confidence: 99%